Development of a FPGA-Based Photovoltaic Panel Emulator Based on a DC/DC Converter - Ickilli, Damla; Can, Hayrettin; Parlak, Koray S. (Ieee, 2012)
Being electrically similar to PV panels, photovoltaic (PV) emulator systems make it possible to perform different PV system tests under various operating conditions. In this paper, we present a photovoltaic emulator system based on a dc/dc converter. Our model can handle the dependence of all the parameters in the model with respect to solar irradiation and temperature. The proposed emulator system is controlled by an Altera Cyclone-III FPGA development board. The experimental results show that the output characteristics of the emulator have good agreement with those of the actual photovoltaic panel in various loads and environmental conditions.
38th IEEE Photovoltaic Specialists Conference (PVSC) -- JUN 03-08, 2012 -- Austin, TX
Keywords: DC-DC power converters; field programmable gate arrays; photovoltaic cells; photovoltaic systems